Acute abdomen due to rupture of a solitary non-parasitic liver cyst - Gutiérrez, Fernando; Toledo, Nancy; Paperán, Juan; Sarubbo, Luis (Cirugía del Uruguay, 1986)
The case ol a palien! that was operated on with clinical diagnosis ol peritonitis due to a perforated gastroduodenal ulcer is presentad. Al operation a non parasilic cyst of the lelt hepatic lobe open in peritoneum, was found. The opening was completad and the cyst evacuated. This paper is presentad in consideration to the excepcional complication of this disease.